Are tachoclines important for solar and stellar dynamos? What can we learn from global simulations. Issue Volume 12:Issue S328(2016) (12th September 2017) - Guerrero, G.; Smolarkiewicz, P. K.; de Gouveia Dal Pino, E. M.; Kosovichev, A. G.; Zaire, B.; Mansour, N. N.
Abstract: The role of tachoclines, the thin shear layers that separate solid body from differential rotation in the interior of late-type stars, in stellar dynamos is still controversial. In this work we discuss their relevance in view of recent results from global dynamo simulations performed with the EULAG-MHD code. The models have solar-like stratification and different rotation rates (i.e., different Rossby number). Three arguments supporting the key role of tachoclines are presented: the solar dynamo cycle period, the origin of torsional oscillations and the scaling law of stellar magnetic fields as function of the Rossby number. This scaling shows a regime where the field strength increases with the rotation and a saturated regime for fast rotating stars. These properties are better reproduced by models that consider the convection zone and a fraction of the radiative core, naturally developing a tachocline, than by those that consider only the convection zone.